Analysis on waterproofing design in CCS pump building of PWR under main feed water pipe broken accident. (July 2022) - Zhao, Haiqi; Lu, Daogang; Zhang, Yuhao; Chen, Zijia; Liang, Jiangtao
Abstract: Component cooling water system (CCS) pump building is an important building connecting nuclear island and conventional island in pressurized water reactor (PWR). When main feed water pipe which crosses through CCS pump building breaks, large amount of fluid leakage may cause flooding hazard to the important equipment in CCS pump building. It is necessary to carry out waterproofing design for the safety of CCS pump building. Usually, important equipment in CCS pump building is designed with a certain height of waterproofing base, which needs to be further verified. It is almost impossible to conduct experimental analysis due to the large size and complex structures of CCS pump building. In the present work, numerical simulation was used to analyze the waterproofing ability of CCS pump building under main feed water pipe broken accident. Calculation method was verified by experiment. It shows that large amount of fluid accumulates in CCS pump building. For more serious flooding condition, water level around CCS pumps reaches 861 mm which exceeds the height of existing CCS pump waterproofing base. A waterproofing improvement design was proposed for CCS pump building of AP1000-type PWR, which feasibility was also analyzed by numerical simulation.